a Pemeriksaan Komposisi Tubuh Bioelectrical Impedance AnalysisBioelectrical (BIA) dan Pengenalan Carbohydrate Loading pada Anggota Ekstrakurikuler Basket - Alfian Abdul Rajab; Mulya Agustina; Efina Amanda; Elita Endah Mawarni (LKP KARYA PRIMA KURSUS, 2026)
Members of the basketball club lacked an understanding of body composition and its relationship to sports performance. They had never undergone an objective body composition assessment. Their knowledge of sports nutrition, particularly the role of carbohydrates and the concept of carbohydrate loading, remained limited. The purpose of this activity was to conduct body composition assessments using Bioelectrical Impedance Analysis (BIA), accompanied by counseling and a simple introduction to the concept of carbohydrate loading. The activity was implemented through sports nutrition counseling and body composition measurements using Bioelectrical Impedance Analysis (BIA). Evaluation was conducted using pre- and post-tests. The target group was 19 students participating in the basketball club. The community service program resulted in 73.7% of participants with good nutritional status, 26.5% body fat percentage, and an average BMR of 1252 kcal. Participants' test scores increased from 66.4 to 75.7 at the post-test. Therefore, the implementation of carbohydrate loading, supported by anthropometric and body composition data, can assist athletes in developing more effective nutritional strategies tailored to individual needs, to optimally support training and competition.